Live-cell imaging of phosphatidic acid dynamics in pollen tubes visualized by Spo20p-derived biosensor - Potocký, Martin; Pleskot, Roman; Pejchar, Přemysl; Vitale, Nicolas; Kost, Benedikt; Žárský, Viktor (The New phytologist, 2014)
Although phosphatidic acid (PA) is structurally the simplest membrane phospholipid, it has been implicated in the regulation of many cellular events, including cytoskeletal dynamics, membrane trafficking and stress responses. Plant PA shows rapid turnover but the information about its spatio-temporal distribution in plant cells is missing. Here we demonstrate the use of a lipid biosensor that enables us to monitor PA dynamics in plant cells. The biosensor consists of a PA-binding domain of yeast SNARE Spo20p fused to fluorescent proteins. Live-cell imaging of PA dynamics in transiently transformed tobacco (Nicotiana tabacum) pollen tubes was performed using confocal laser scanning microscopy. In growing pollen tubes, PA shows distinct annulus-like fluorescence pattern in the plasma membrane behind the extreme tip. Coexpression studies with markers for other plasmalemma signaling lipids phosphatidylinositol 4,5-bisphosphate and diacylglycerol revealed limited colocalization at the shoulders of the apex. PA distribution and concentrations show distinct responses to various lipid signaling inhibitors. Fluorescence recovery after photobleaching (FRAP) analysis suggests high PA turnover in the plasma membrane. Our data show that a biosensor based on the Spo20p-PA binding domain is suitable for live-cell imaging of PA also in plant cells. In tobacco pollen tubes, distinct subapical PA maximum corroborates its involvement in the regulation of endocytosis and actin dynamics.
Keywords: Qb-SNARE Proteins; Cell Membrane; počítačové zpracování obrazu; Nicotiana tabacum (tobacco); Diglycerides; Phospholipase D; Phosphatidylinositol 4,5-Diphosphate; Photobleaching; proteiny Qb-SNARE; Recombinant Fusion Proteins; Saccharomyces cerevisiae Proteins; phosphatidic acid (PA); Binding Sites; biosenzitivní techniky; Phosphatidic Acids; fotovybělování; proteiny Qc-SNARE; rekombinantní fúzní proteiny; tabák; fosfolipasa D; Fluorescence; diglyceridy; fosfatidylinositol-4,5-difosfát; buněčná membrána; Spo20p; Pollen Tube; phospholipase D; pylová láčka; vazebná místa; Nicotiana; live-cell microscopy; pollen tube; Saccharomyces cerevisiae - proteiny; Biosensing Techniques; fluorescence; kyseliny fosfatidové; Image Processing, Computer-Assisted; Qc-SNARE Proteins